Monitoring the quality of hormonal contraceptives distributed by the State Secretary of Health of São Paulo during the period comprised betwe - E. O. Markman, Blanca (2011)
The distribution and quality assurance of medicines are under Pharmaceutical Care responsibility. The prevalence of oral contraceptives in Brazil is the third highest in Latin America.where access to contraceptives have increased significantly since the establishment of the Program of 2 Assistance Health Care for Women . In 2007 the State Secretary of Health Department implemented the Quality Monitoring of Contraceptives purchased and distributed by this Department. This study aims to demonstrate, through the results achieved, the quality of these contraceptives. The tests performed followed the official codes and manufacturers' specifications. 154 samples of contraceptives were analyzed, , showing, 71% of samples as satisfactory and 29% as unsatisfactory. The quality deviations found initially were overcome in subsequent batch analysis. Continuous monitoring of quality is necessary in the acquisition of new lots. These results subsidize the National Agency of Sanitary Surveillance in the sanitation of the Brazilian pharmaceutical market in order to prevent health hazards, promoting a political and social support action on the voluntary regulation of reproduction